(untitled) (London Journal of Medical and Health Research, 2024)
In Brazil, it is estimated that 2 million people live with dementia syndromes, with a tendency to triple by 2050, according to the Global Burden of Disease. At the same time, Vigitel found that 20.8% of the population will consume alcohol excessively in 2023. In view of this, it is important to elucidate the relationship between alcohol and dementia in the elderly. This study aims to assess the relationship between alcohol consumption throughout life and the impact on neurocognition in the elderly. Using the descriptors "aged", "dementia" and "ethanol" with the operator AND in the PubMed, VHL and Cochrane databases, associated with the inclusion criteria of publication in the last 20 years, availability in full and English, Portuguese or Spanish language, 9 studies were selected, after excluding duplicates and analyzing titles and abstracts. Of the studies reviewed, 4 found an association between light to moderate alcohol consumption and a lower risk of developing and progressing dementia, while 2 had inconclusive findings. With regard to high consumption, 3 studies found no statistically significant relationship with dementia, and 4 associated this amount of alcohol with a higher risk of developing and progressing the condition. This review suggests that light to moderate alcohol consumption may be associated with a lower likelihood of developing or progressing to dementia, while findings on the effects of high consumption are divergent, yet most recent evidence points to the pathological role of this amount of alcohol consumption on cognition. The need for more research is highlighted, especially with samples from the Brazilian population, since none of the studies found were Brazilian.